How immigrants fare across the earnings distribution: international analyses - Barry R. Chiswick; Anh Tram Le; Paul W. Miller (Institute for the Study of Labor (IZA), 2006)
This paper applies the quantile regression methodology to the study of the determinants of the distribution of earnings among the native born and immigrants in the United States and Australia. The analysis for immigrants is performed separately for those from English-speaking and non-English speaking origins. Using Census data, the quantile regressions permit the measurement of the partial effect of explanatory variables (such as schooling and experience) and the native born-immigrant earnings differential at the different deciles of the earnings distribution. Among other findings, the effects on earnings of schooling and labor market experience are shown to increase at higher deciles. The native-immigrant earnings gap varies by decile, and in particular increases in the U.S. at higher deciles. Minimum wages in the U.S. appear to compress earnings at low deciles, while the Australian minimum (administered) wage system appears to compress earnings across the distribution of earnings.
urn:nbn:de:101:1-2009031348
Keywords: 330